Truth, Racial Healing, And Transformation: - Heath Brown (Journal of Social Equity and Public Administration, 2024)
The public policy process in the United States has strong status quo biases that frustrate efforts to adopt policies focused on racial justice and social equity. On occasion, a policy window opens and the chance for real change increases greatly. This article is a case study focused on advocacy for a Truth, Racial Healing, and Transformation (TRHT) Commission during an open policy window that occurred in 2020 related to brutal police violence (readers should know in advance that traumatic events covered in this article include descriptions of racial violence). The findings are drawn primarily from original interviews with advocates for the Commission, providing an outsider’s perspective on this political process.